Адміністративні процедури виконання судового рішення в адміністративному судочинстві: питання сьогодення - Шатрава, С. О.; Shatrava, S. O.; ORCID: http://orcid.org/0000-0002-7072-961X (Право і безпека. – 2014. - № 2 (53). – С. 75-80, 2014)
Виокремлено адміністративні процедури виконання судового рішення в адміністративному судочинстві, спрямовані на захист прав, свобод, законних інтересів фізичних і юридичних осіб. Надано власне розуміння терміна «виконання судових рішень в адміністративному судочинстві» та виокремлено особливості зазначених процедур. Доведено, що із запровадженням адміністративного судочинства судова практика виявила недостатність положень Закону України «Про виконавче провадження» для ефективного виконання судових рішень в адміністративних справах, оскільки виконання судових рішень адміністративних судів вимагає вироблення спеціальних процедур у виконавчому провадженні. Наголошено, що механізм виконання судових рішень в адміністративних справах потребує ґрунтовної розробки та відповідного законодавчого врегулювання.

Administrative procedures to enforce the judgment in administrative proceedings aimed at protecting the rights, freedoms and legitimate interests of individuals and legal entities are singled out in the article. On the basis of the analysis of the Code of Administrative Proceedings of Ukraine and the Law of Ukraine «On Enforcement Proceedings» the author has singled out that the procedure to enforce the judgment in an administrative case has the following stages: 1) preparation; 2) enforcement of proceedings and preparation for direct execution; 3) realization of enforcement proceedings; 4) completion of enforcement proceedings. Own understanding of the term «enforcement of judgments in administrative proceedings» as a set of related court proceedings, government entities, their officials and individuals and legal entities addressed to the direct realization of the rights, freedoms and interests of individuals and legal entities and fulfilling the duties by all members of the administrative process is presented. Features of administrative procedures to enforce a judgment in the administrative proceedings are singled out, namely they are: a beginning in court agencies and prolongation in the executive authorities; different execution term; legal regulation by the Code of Administrative Proceedings of Ukraine and the Law of Ukraine «On Enforcement Proceedings»; absence of an effective system of court control over the progress of a judgment; opportunity to end as a reconciliation; voluntary and compulsory order of executing a judgment; absence of an effective mechanism for voluntary execution of a judgment. It is proved that implementation of administrative proceedings made possible for court practice to reveal insufficiency of the Law of Ukraine «On Enforcement Proceedings» for effective execution of judgments in administrative cases as enforcement of judgments of administrative courts requires the development of special procedures in the enforcement proceedings. It is emphasized that the mechanism of judgments’ enforcement in administrative cases requires substantial development and appropriate legislative regulation.

Выделены административные процедуры исполнения судебного решения в административном судопроизводстве, которые направлены на защиту прав, свобод, законных интересов физических и юридических лиц. Предоставлено собственное понимание термина «исполнение судебных решений в административном судопроизводстве» и выделены особенности указанных процедур. Доказано, что с введением административного судопроизводства судебная практика выявила недостаточность положений Закона Украины «Об исполнительном производстве» для эффективного исполнения судебных решений по административным делам, поскольку выполнение судебных решений административных судов требует выработки специальных процедур в исполнительном производстве. Отмечено, что механизм исполнения судебных решений по административным делам требует основательной разработки и соответствующего законодательного урегулирования.
Administrative procedures of judgment’s enforcement in administrative proceedings: issues of today
Административные процедуры исполнения судебного решения в административном судопроизводстве: вопрос сегодняшнего дня
Шатрава С. О. Адміністративні процедури виконання судового рішення в адміністративному судочинстві: питання сьогодення / С. О. Шатрава // Право і Безпека. - 2014. - № 2 (53). - С. 75-80.
Шатрава С. О. "Адміністративні процедури виконання судового рішення в адміністративному судочинстві: питання сьогодення." Право і Безпека 2 (2014): 75-80.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; адміністративні процедури; адміністративне судочинство; судове рішення; виконання судових рішень; стадія провадження; administrative procedures; administrative proceedings; judgment; execution; stage of the proceedings; административные процедуры; административное судопроизводство; судебное решение; исполнение судебных решений; стадии производства